PENGEMBANGAN MEDIA ECONINGBOX BERBASIS UNPLUGGED CODING UNTUK MENSTIMULASI KEMAMPUAN BERFIKIR LOGIS ANAK USIA 5-6 TAHUN - Silvi Ifatur Rohmah; Yes Matheos Lasarus Malaikosa; Mallevi Agustin Ningrum; Dhian Gowinda Luh Safitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of logical thinking skills among 5-6 year old children at ADNI Kindergarten. Logical thinking is a stage of thinking that requires logical abilities in accordance with reality, as well as reasonable thinking. This study focuses on the indicators of classification and pattern recognition. The purpose of this study is to determine the validity, practicality, and effectiveness of the econingbox media in stimulating the logical thinking skills of 5-6 year old children. This study uses a research and development method with the ADDIE model. The targets of this study are children in group B aged 5-6 years at ADNI Kindergarten, Harapan Ibu Kindergarten, and Al-Hikmah Kindergarten. The research data was based on the results of descriptive statistical analysis of the children's learning outcomes at the three institutions using the econingbox media. The validity results from the subject matter experts obtained a percentage of 90.91% with a category of very feasible. Meanwhile, the validity results from the media experts obtained a percentage of 100% with a category of very feasible. The results of the media practicality test by teachers at the first and second institutions obtained a percentage of 92.86%, with a category of very practical. Meanwhile, the results of the practicality test by teachers at the third institution obtained a percentage of 89.29%, with a category of very practical. Based on the results of descriptive statistics, the three institutions sampled in the study showed that the average learning outcomes of children were above 75, reinforced by the Sing. (2-tiled) value from the one-way ANOVA test of 0.027, which is less than 0.05. Based on this, it can be concluded that the Econingbox media is effective in stimulating the logical thinking abilities of children aged 5-6 years.